The role of rhizofiltration and allelopathy on the removal of cyanobacteria in a continuous flow system - Castro-Castellon, AT; Hughes, JMR; Read, DS; Azimi, Y; Chipps, MJ; Hankins, NP (Springer, 2021)
A continuous flow filtration system was designed to identify and quantify the removal mechanisms of Cyanobacteria (Microcystis aeruginosa) by hydroponic biofilters of Phalaris arundinacea compared to synthetic filters. The filtration units were continuously fed under plug-flow conditions with Microcystis grown in photobioreactors. Microcystis cells decreased at the two flow rates studied (1.2 ± 0.2 and 54 ± 3 cm3 minˉ1) and results suggested physical and chemical/biological removal mechanisms were involved. Physical interception and deposition was the main removal mechanism with packing density of the media driving the extent of cell removal at high flow, whilst physical and chemical/biological mechanisms were involved at low flow. At low flow, the biofilters decreased Microcystis cell numbers by 70% compared to the controls. The decrease in cell numbers in the biofilters was accompanied by a chlorotic process (loss of green colour), suggesting oxidative processes by the release of allelochemicals from the biofilters.